Pengembangan Model Praktikum Kimia Berbasis Green Chemistry dengan Metode Inkuiri Terbimbing Pada Madrasah Aliyah - Imam Darmawan; Supartono Supartono; Endang Susilaningsih (Al Makki Publisher, 2023)
The existence of schools that were quite far from the city center and industry area such as private Madrasah Aliyah. Generally, these schools did not have lab facility and its learning process is only by delivering materials without any practicum. Researcher did a research development Practicum Model of Chemistry based Green Chemistry with guided inquiry method in MA Annur Setupatok. The results of the research showed that there was a rising students’s concept understanding showed 85.7% After practicum was done, the average of n-gain score was 0,48. It was showed by the average of pre-test and post-test scores. The average of observation result during the practicum was 90.51%, the average of questionnaire sheet result about students’ attitude and responses was 82,3%, the average result of practicality of practicum instrument was 82.3%, and the effectiveness of lab instrument was 65%. Meanwhile, to test the effectiveness of the lab facility, the researcher used comparative test with practicum that used main lab facilities in MA Nusantara. The result of paired-t test calculation showed that t score was -0,67. It was smaller than t-table score, 3.18.